Synthetic gene network : modeling, analysis, and robust design methods - Chen, Bor-Sen; Wang, Yu-Chao, 1981- (CRC Press/Taylor & Francis Group, 2014)
This book develops a rational design and systematic approach to construct a gene network with desired behaviors. In order to achieve this goal, the registry of standard biological parts and experimental techniques are introduced at first. Then these biological components are characterized by a standard modeling method and collected in the component libraries, which can be efficiently reused in engineering synthetic gene networks. Based on the system theory, some design specifications are provided to engineer the synthetic gene networks to robustly track the desired trajectory by employing the component libraries.